Micropropagação de Campomanesia pubescens (DC.) Berg. - Resende, Erivelton (2017)
Gabirobeira, a native plant of the cerrado, produces tasty fruit, being able to have several utilities, in the table, in drinks and, popularly, like medicinal plant. Nowadays, it is a source of income for many communities, and due to the expansion of the agricultural frontier, the development of technologies that allow its domestication becomes necessary. Among the inputs required for the implantation and conduction of productive and profitable plantations, the production of high standard quality sanitary seedlings that reproduce productive plants, coming from the selection of superior genotypes, with desirable agronomic characteristics is very important. Considering that Campomanesia pubescens is an allogama species, the production of seedlings through seed provides heterogeneous seedlings, thereby, the asexual reproduction allows to reproduce individuals identical to the mother plant. The objectives of this study was to verify, in the in vitro multiplication phase of C. pubescens, the influence of the salts concentration of culture medium (MS and WPM) and tcytokinin (BAP), and also, in the in vitro rooting phase, the effect of salt concentrations of WPM medium and IBA auxin. It is concluded that the C. pubescens micropropagation cultivated in the growth room can be done in the culture medium WPM, MS 50% and 100%, adding with 0.5 and 1.0 mg L-1 of BAP and its rooting in 75% of the salt concentration of the supplemented medium of 0.5 and 1.0 mg L-1 of IBA, in two-internode micro-heads.